Content analysis of thinking skills level in reading questions of tenth grade of EFL textbook in Indonesia - Muhsinin, Muhsinin; Sahni, Sahni; Ariawan, Soni; Hamdi, M. Zulpiani (Journal of English Language Teaching Innovations and Materials (Jeltim), 2025)
Textbooks play a pivotal role in education, serving as primary learning resources and guiding both teaching and learning activities. Despite their importance, limited research has examined the cognitive levels of reading comprehension questions in EFL textbooks. This study aimed to analyze the level and distribution of thinking skills reflected in the reading questions of the tenth-grade Indonesian EFL textbook Bahasa Inggris. Utilizing content analysis, the study employed coding tables and checklists based on the revised Bloom"™s Taxonomy, which classifies cognitive skills into six categories: Remember, Understand, Apply, Analyze, Evaluate, and Create. A total of 123 reading questions were analyzed. The results reveal a strong dominance of lower-order thinking skills (LOTS), particularly the Remember category, which accounted for over 60% of all questions. Understand and Apply followed with 15.45% and 13.00%, respectively. Higher-order thinking skills (HOTS) were significantly underrepresented, with Analyze and Evaluate comprising only 1.63%, and no instances of Create were identified. Overall, LOTS constituted 96.74% of the questions, while HOTS made up just 3.24%. These findings indicate a lack of cognitive challenge in the textbook"™s reading sections, highlighting the need for more balanced question design that promotes critical and creative thinking.How to cite this paper: Muhsinin, M., Sahni, S., Ariawan, S., Hamdi, M. Z. (2023). The level of thinking skills in reading questions of tenth grade EFL textbook in Indonesia. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(1), 35"“53. https://doi.org/10.26418/jeltim.v7i1.60800